Organisational contextual aspects among medical social workers - Albrithen, Abdulaziz; Yalli, Nadir (Frontiers in Psychology, 2023)
Since the recognition of social work in health care, the number of social workers has dramatically increased. The proved association between psychosocial conditions and biophysical features encouraged in social work drove its professionalism and made social workers an essential part of the health care team in hospitals. Today, social workers are involved in medicine as specialised practitioners who share their knowledge and care along with other professionals to provide multi-disciplinary interventions and services to people in need. Using a self-administered questionnaires, this study aims to examine the relationship between two organisational-contextual aspects (i.e. organisational structural, and organisational resources) among social workers in health care in Saudi Arabia.